Medici in transizione Etica e identità professionale nella sanità aziendalizzata - Sofritti, Federico (Premio Ricerca «Città di Firenze», 2015)
The evolution of the Italian health system, which went from the establishment of the National Health Service in 1978 to the corporate management introduced with the reforms of the 1990s, requires a thorough knowledge of the effects of organizational change on the medical profession. Starting from this consideration, this volume focuses on the results of the corporatising process in terms of professional identity. The research, conducted among medical specialists operating in the territorial structures of two Tuscan Health Authorities, shows a transitioning figure, which hints at a new form of medical professionalism.